Identification of entacapone as a chemical inhibitor of FTO mediating metabolic regulation through FOXO1 - Peng, Shiming; Xiao, Wen; Ju, Dapeng; Sun, Baofa; Hou, Nannan; Liu, Qianlan; Wang, Yanli; Zhao, Haijiao; Gao, Chunchun; Zhang, Song; Cao, Ran; Li, Pengfei; et al. (Science translational medicine, 2019)
Recent studies have established the involvement of the fat mass and obesity-associated gene ( ) in metabolic disorders such as obesity and diabetes. However, the precise molecular mechanism by which FTO regulates metabolism remains unknown. Here, we used a structure-based virtual screening of U.S. Food and Drug Administration-approved drugs to identify entacapone as a potential FTO inhibitor. Using structural and biochemical studies, we showed that entacapone directly bound to FTO and inhibited FTO activity in vitro. Furthermore, entacapone administration reduced body weight and lowered fasting blood glucose concentrations in diet-induced obese mice. We identified the transcription factor forkhead box protein O1 ( ) mRNA as a direct substrate of FTO, and demonstrated that entacapone elicited its effects on gluconeogenesis in the liver and thermogenesis in adipose tissues in mice by acting on an regulatory axis.